Assessment of the temporal trend and daily profiles of the dietary purine intake among Chinese residents during 2014 to 2021 - Li, Shiwen; Liu, Xin; Jia, Xiwu; Fang, Min; Yang, Qing; Gong, Zhiyong (Frontiers in Nutrition, 2023)
The incidence of hyperuricemia is on the rise in China, primarily due to dietary habits. However, limited data exists regarding dietary purine intake in the country. This study aimed to estimate the daily dietary purine intake among Chinese residents from 2014 to 2021 and evaluate the temporal trend using joinpoint regression analysis. The analysis revealed an annual percentage change (APC) of 0.8% (95%CI: 0.1%-1.5%) in dietary purine intake prior to the joinpoint (2014-2019). Following the joinpoint (2019-2021), the APC significantly increased to 6.5% (95%CI: 3.3%-9.8%), indicating a noteworthy upward trend (P=0.045). Furthermore, the average daily purine intake varied significantly among different regions of China, with the southern region showing the highest dietary intake of purines. Considering the diverse contributions of various food sources to dietary purine intake, it was observed that meat consumption had the greatest impact, accounting for 36.2% of purine intake, followed by cereals consumption (25.3%) and vegetables and edible fungi (24.2%). These findings hold significance for dietary intervention and management strategies aimed at reducing purine intake among the population.